THE EFFECT OF USING COLORFUL PICTURES TOWARD STUDENTS’ ENGLISH VOCABULARY MASTERY AT THE FIRST GRADE STUDENTS OF SMK - Soleha, Maratus (Universitas Muhammadiyah Lampung, 2022)
This research is aimed to find out the effect of using colorful pictures toward students’ English vocabulary mastery at the first grade students of SMK. The research was experimental. The population of the research was of the first grade students of SMK. The sample of the research was 64 students. The sample was taken by using cluster random sampling technique. The technique that was used to analysis the data is formula. The finding shows that the score of (3.27) is higher than (1.669) from (df) 62. Based on the result of the study, it can be concluded that colorful pictures has positive effect toward students’ English vocabulary mastery at the first grade students of SMK. Dealing with the result, it is suggested that teacher to use colorful pictures toward students’ English vocabulary mastery because it can improve students vocabulary at the first grade students.